Dietary niacin intake and epilepsy: a cross-sectional study - Ken Ling; Xinghui He; Zhiquan Yang (Epilepsy & Behavior Reports)
This study aimed to examine the association between dietary niacin intake and the prevalence of epilepsy. We conducted a cross-sectional analysis of 14,236 participants from the National Health and Nutrition Examination Survey (NHANES) 2013–2018. Multivariable logistic regression, generalized additive models, and subgroup analyses were employed to assess the relationship. An inverse association was found between dietary niacin intake and the prevalence of epilepsy: for every 10 mg/day increase, the odds of having epilepsy were reduced by 15 % (OR = 0.85, p = 0.0266). Participants in the highest quintile of niacin intake had a significantly lower odds of epilepsy compared to those in the lowest quintile (OR = 0.45, p = 0.0187). This negative association remained consistent across groups with diverse demographic characteristics, medical conditions, and lifestyle choices. Our findings suggest a possible inverse association between dietary niacin intake and the prevalence of epilepsy.